The Impact of Human Service Provider Quality on the Personal Outcomes of People With Intellectual and Developmental Disabilities - Friedman, Carli (Frontiers in Rehabilitation Sciences, 2022)
Background: Quality of life is multidimensional – influenced by individual, organizational, and environmental factors. As such, when examining personal outcomes, it is also important to consider meso and macro factors that contribute to people with intellectual and developmental disabilities’ (IDD’s) quality of life. While it is widely acknowledged that organizational factors contribute to people’s quality of life, there is less research directly examining how the quality of human service providers contributes to people with IDD’s personal outcomes. For these reasons, the aim of this study was to explore the relationship between provider quality and people with IDD’s personal quality of life outcomes. Methods: Using a multilevel linear regression we analyzed secondary Personal Outcome Measures® (personal outcomes) and Basic Assurances® (provider quality) data from 2,900 people with IDD served by 331 human service providers. Results: People with IDD’s personal outcomes, regardless of their support needs or other demographics, were significantly impacted by the quality of the human service providers they received services from – the higher the quality of the provider, the more personal outcomes they had present. In addition, the following demographic covariates were correlated with personal outcomes: gender; race; complex support needs; residence type; and organizations that offered therapy services. Discussion: While quality improvement initiatives may require a great deal of cost and time commitment from providers, our findings suggest the effort translates to improved personal outcomes among people with IDD. The ultimate goal of service providers should be improvement of quality of life among those they support.